THE EFFECT OF FINANCIAL PRESSURE ON TAX AVOIDANCE WITH MODERATION OF CSR DISCLOSURE - Kusuma, Caroline Patricia; Santoso, Eko Budi (Jurnal Aplikasi Akuntansi, 2025)
Taxes hold an important role as the main source of state revenue that contributes to national development. The decline in the ratio of tax revenue to Indonesia's GDP indicates the potential for tax avoidance practices. Therefore, this study is conducted to analyze the effect of financial pressure on tax avoidance, and the contribution of CSR disclosure as moderation. Financial pressure is measured through three indicators, namely financial targets, external pressures, and financial stability. The subject of study is companies in the energy and raw materials sectors listed on the IDX during 2020-2023. The study results show that financial targets have a significant positive effect on tax avoidance, while external pressure has a significant negative effect. In contrast, tax avoidance is not significantly affected by financial stability. Further findings prove if CSR disclosure is able to weaken the influence of financial targets and external pressures on tax avoidance, but CSR cannot moderate the influence of financial stability on tax avoidance. This study contributes to enriching the literature on tax avoidance and implies practically that the substantial application of CSR in business practices can help reduce tax avoidance and encourage companies to be more consistent in carrying out their social responsibilities.